Difference between revisions of "022 Sample Final A, Problem 1"

From Math Wiki
Jump to navigation Jump to search
Line 22: Line 22:
 
|
 
|
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\frac{\partial}{\partial x} f(x, y) & = & \frac{\partial}{\partial x} \left( \frac{2xy}{x - y}\right)\\
+
\displaystyle{\frac{\partial}{\partial x} f(x, y)} & = & \displaystyle{\frac{\partial}{\partial x} \left( \frac{2xy}{x - y}\right)}\\
& = & \frac{2y(x - y) -2xy}{(x - y)^2}\\
+
&&\\
& = & \frac{-2y^2}{(x - y)^2}
+
& = & \displaystyle{\frac{2y(x - y) -2xy}{(x - y)^2}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{-2y^2}{(x - y)^2}}
 
\end{array}</math>  
 
\end{array}</math>  
 
|-
 
|-
Line 31: Line 33:
 
|
 
|
 
::<math>\begin{array}{rcl}
 
::<math>\begin{array}{rcl}
\frac{\partial}{\partial y}f(x, y) & = & \frac{\partial}{\partial y}\left(\frac{2xy}{x - y}\right)\\
+
\displaystyle{\frac{\partial}{\partial y}f(x, y)} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{2xy}{x - y}\right)}\\
& = & \frac{2x(x - y) +2xy}{(x - y)^2}\\
+
&&\\
& = & \frac{2x^2}{(x - y)^2}
+
& = & \displaystyle{\frac{2x(x - y) +2xy}{(x - y)^2}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{2x^2}{(x - y)^2}}
 
\end{array}</math>  
 
\end{array}</math>  
 
|}
 
|}
Line 44: Line 48:
 
|
 
|
 
<math>\begin{array}{rcl}
 
<math>\begin{array}{rcl}
\frac{\partial}{\partial x} \frac{\partial f(x, y)}{\partial x} & = & \frac{\partial}{\partial x}\left(\frac{-2y^2}{(x - y)^2}\right)\\
+
\displaystyle{\frac{\partial}{\partial x} \frac{\partial f(x, y)}{\partial x}} & = & \displaystyle{\frac{\partial}{\partial x}\left(\frac{-2y^2}{(x - y)^2}\right)}\\
& = & \frac{0 - 2(x - y)(-2y^2)}{(x - y)^4}\\
+
&&\\
& = & \frac{4xy^2 - 4y^3}{(x - y)^4}
+
& = & \displaystyle{\frac{0 - 2(x - y)(-2y^2)}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4xy^2 - 4y^3}{(x - y)^4}}
 
\end{array}</math>
 
\end{array}</math>
 
|-
 
|-
 
|
 
|
 
<math>\begin{array}{rcl}
 
<math>\begin{array}{rcl}
\frac{\partial}{\partial y} \frac{\partial f(x, y)}{\partial x} & = & \frac{\partial}{\partial y}\left(\frac{-2y^2}{(x - y)^2}\right)\\
+
\displaystyle{\frac{\partial}{\partial y} \frac{\partial f(x, y)}{\partial x}} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{-2y^2}{(x - y)^2}\right)}\\
& = & \frac{-4y(x - y)^2 -4y^2(x - y)}{(x - y)^4}\\
+
&&\\
& = & \frac{-4y(x^2 - 2xy + y^2) - 4xy^2 + 4y^3}{(x - y)^4}\\
+
& = & \displaystyle{\frac{-4y(x - y)^2 -4y^2(x - y)}{(x - y)^4}}\\
& = & \frac{4xy^2 - 4x^2y}{(x - y)^4}
+
&&\\
 +
& = & \displaystyle{\frac{-4y(x^2 - 2xy + y^2) - 4xy^2 + 4y^3}{(x - y)^4}}\\
 +
& = & \displaystyle{\frac{4xy^2 - 4x^2y}{(x - y)^4}}
 
\end{array}</math>
 
\end{array}</math>
 
|-
 
|-
 
|
 
|
 
<math>\begin{array}{rcl}
 
<math>\begin{array}{rcl}
\frac{\partial}{\partial x} \frac{\partial f(x, y)}{\partial y} & = & \frac{\partial}{\partial x}\left(\frac{2x^2}{(x - y)^2}\right)\\
+
\displaystyle{\frac{\partial}{\partial x} \frac{\partial f(x, y)}{\partial y}} & = & \displaystyle{\frac{\partial}{\partial x}\left(\frac{2x^2}{(x - y)^2}\right)}\\
& = & \frac{4x(x - y)^2 -2(x - y)2x^2}{(x - y)^4}\\
+
&&\\
& = & \frac{4x(x^2 - 2xy + y^2) -4x^3+ 4x^2y}{(x - y)^4}\\
+
& = & \displaystyle{\frac{4x(x - y)^2 -2(x - y)2x^2}{(x - y)^4}}\\
& = & \frac{4xy^2 -4x^2y}{(x - y)^4}
+
&&\\
 +
& = & \displaystyle{\frac{4x(x^2 - 2xy + y^2) -4x^3+ 4x^2y}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4xy^2 -4x^2y}{(x - y)^4}}
 
\end{array}</math>
 
\end{array}</math>
 
|-
 
|-
Line 68: Line 79:
  
 
<math>\begin{array}{rcl}
 
<math>\begin{array}{rcl}
\frac{\partial}{\partial y} \frac{\partial f(x, y)}{\partial y} & = & \frac{\partial}{\partial y}\left(\frac{2x^2}{(x - y)^2}\right)\\
+
\displaystyle{\frac{\partial}{\partial y} \frac{\partial f(x, y)}{\partial y}} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{2x^2}{(x - y)^2}\right)}\\
& = & \frac{0 + 2(x - y)(2x^2)}{(x - y)^4}\\
+
&&\\
& = & \frac{4x^3 - 4x^2y}{(x - y)^4}
+
& = & \displaystyle{\frac{0 + 2(x - y)(2x^2)}{(x - y)^4}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{4x^3 - 4x^2y}{(x - y)^4}}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 77: Line 90:
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|<math>\frac{\partial}{\partial x} f(x, y) = \frac{-2y^2}{(x - y)^2} \qquad
+
|<math>\displaystyle{\frac{\partial}{\partial x} f(x, y) = \frac{-2y^2}{(x - y)^2} \qquad
\frac{\partial}{\partial y} f(x, y) = \frac{2x^2}{(x - y)^2} \qquad</math>
+
\frac{\partial}{\partial y} f(x, y) = \frac{2x^2}{(x - y)^2} \qquad}</math>
 
|-
 
|-
 
|
 
|
<math>\frac{\partial}{\partial x} \frac{\partial f(x, y)}{\partial x} = \frac{4xy^2 - 4y^3}{(x - y)^4} \qquad
+
<math>\displaystyle{\frac{\partial}{\partial x} \frac{\partial f(x, y)}{\partial x} = \frac{4xy^2 - 4y^3}{(x - y)^4} \qquad
 
\frac{\partial}{\partial y}\frac{\partial f(x, y)}{\partial x} = \frac{4xy^2 - 4x^2y}{(x - y)^4} \qquad
 
\frac{\partial}{\partial y}\frac{\partial f(x, y)}{\partial x} = \frac{4xy^2 - 4x^2y}{(x - y)^4} \qquad
 
\frac{\partial}{\partial x}\frac{\partial f(x, y)}{\partial y} = \frac{4xy^2 -4x^2y}{(x - y)^4} \qquad
 
\frac{\partial}{\partial x}\frac{\partial f(x, y)}{\partial y} = \frac{4xy^2 -4x^2y}{(x - y)^4} \qquad
\frac{\partial}{\partial y}\frac{\partial f(x, y)}{\partial y} = \frac{4x^3 - 4x^2y}{(x - y)^4}
+
\frac{\partial}{\partial y}\frac{\partial f(x, y)}{\partial y} = \frac{4x^3 - 4x^2y}{(x - y)^4}}
 
</math>
 
</math>
 
|}
 
|}
 
[[022_Sample_Final_A|'''<u>Return to Sample Exam</u>''']]
 
[[022_Sample_Final_A|'''<u>Return to Sample Exam</u>''']]

Revision as of 14:11, 6 June 2015

Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function


Foundations:  
1)Which derivative rules do you have to use for this problem?
2)What is the partial derivative of xy, with respect to x?
1)You have to use the quotient rule, and product rule. The quotient rule says that ,   so . The product rule says .   This means
2) The partial derivative is y, since we treat anything not involving x as a constant and take the derivative with respect to x. So

Solution:

Step 1:  
First, we start by finding the first partial derivatives. So we have to take the partial derivative of f(x, y)with respect to x, and the partial derivative of f(x, y)with respect to y. This gives us the following:
This gives us the derivative with respect to x. To find the derivative with respect to y, we do the following:
Step 2:  
Now we have to find the 4 second derivatives:

Final Answer:  

Return to Sample Exam